Gradient Outbreak of Coconut Slug Caterpillar, Macroplectra nararia Moore in East Coast of India - Rajan, P.; Josephrajkumar, A.; Sujatha, A. (International Coconut Community Journal, 2011)
Gradient outbreak of coconut slug caterpillar. Macroplectra nararia Moore (Limacodidae: Lepidoptera) in East Godavari district, Andhra Pradesh during April-May 2009 is closely interlinked with rise in ambient temperature and humidity along the water bodies. This favoured large scale explosion of pest population leading to widespread damage in coconut plantations ranging from 90-95% in severely affected gardens, indicating the sporadic nature of the pest. Exacerbation by grey leaf blight fungus, Pestalotiopsis palmarum accelerated the damage causing rampant scorching of coconut leaflets in pest affected gardens. In the field, some caterpillars were found infected by entomopathogens. Light trapping is suggested as an effective monitoring tool and a feasible mechanical control strategy of the pest.